Scenarios of business development in the agricultural machinery market under conditions of international trade integration - Tatiana N. Litvinova; Galina A. Khmeleva; Lilia V. Ermolina; Tatiana V. Alferova; Irina V. Cheryomushkina (Contemporary Economics, 2016)
The purpose of the article is to identify and analyze scenarios of business development in the agricultural machinery market under conditions of international trade integration using the case of present-day Russia and to determine the need for state support for domestic production. As a methodological provision, we use the scenario analysis method adapted by the authors for the determination and analysis of possible scenarios of business development in the agricultural machinery market under conditions of international trade integration. From the research results, the authors conclude that the Russian agricultural machinery market develops dynamically under the influence of multiple favorable factors and positive tendencies, which include a population's income growth, increases in crop areas of farm crops, and state agricultural machinery modernization programs, among other. In view of recent events in the currency market, Russian manufacturers of agricultural machinery are presented with better opportunities to export their products. The performed analysis of features of the Russian agricultural machinery market under conditions of international trade integration shows that increased demand and market prices are probable and that this could lead to enterprise income growth. From our scenario analysis of business development in the agricultural machinery market under conditions of international trade integration, we identify the absence of an urgent need for state interference in market processes in the Russian market for agricultural machinery in the next five years.
Keywords: Q17; 330; business development; agricultural machinery market; international trade integration; scenario analysis